SCHIFFRIN, DEBORAH, TANNEN, DEBORAH y HEIDI E, HAMILTON (Comps.). (2001). The handbook of discourse analysis - Kaplan, Nora (Revista Latinoamericana de Estudios del Discurso, 2020)
SCHIFFRIN, DEBORAH, TANNEN, DEBORAH y HEIDI E, HAMILTON (Comps.). (2001). The handbook of discourse analysis. Malden, Mass.: Blackwell Publishers. xx + 851 pp. ISBN 0-631-20595-0.